INTERPRETATION OF SUTAN TAKDIR ALISJAHBANA'S NOVEL "DIAN YANG TAK KUNJUNG PADAM" - Jafar Lantowa (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to uncover the implicit meaning contained in Sutan Takdir Alisjahbana’s novel Dian yang Tak Kunjung Padam through Yuri Lotman's semiotic approach. The first edition of this novel was published in 2007 by Dian Rakyat with a total of 156 pages. The method used in this study was qualitative method. The data were collected from two sources, namely intra textual data which was Sutan Takdir Alisjahbana’s novel Dian yang Tak Kunjung Padam and extra textual data which were correlated to the novel. The results showed that the structure of the novel was formed by semantic units in the form of binary oppositions which were equivalent to each other. The semantic units led to an archiseme which was a spatial form of the aristocracy view of life namely longing vs. hate. In the novel, the aristocracy view of life in Palembang society was placed in opposition to the structure of another view of life, the proletariat. The later was evaluated based on the aristocracy. The codes of aristocracy and proletariat in the text of the novel were related to those outside the text. The main semantic units of Palembang aristocracy are bilateral vs. personal and wealth vs. love.